Analisis Putusan Mahkamah Konstitusi Nomor 20/PUU-XIV/2016 Tentang Perekaman yang Dilakukan Secara Tidak Sah - Juliani Juliani (TANFIDZIY, 2022)
This thesis describes the Analysis of the Decision of the Constitutional Court Number 20/PUU-XIV/2016 regarding the illegal trial. Initially, the circulation of a recording of a conversation allegedly heard between Setya Novanto and Ma'roef Sjamsudin (Principal Director of PT. Freeport Indonesia) was recorded secretly without the knowledge of the relevant parties. This type of research is normative juridical using secondary data consisting of primary legal materials and secondary legal materials. The results of the study explain that, the Basis and Considerations of the Constitutional Court Decision Number 20/PUU-XIV/2016 concerning Illegal Recordings is declared rejected, because what is disputed by the Petitioner has been fulfilled by the ITE Law, especially Article 31 paragraph (3 ) Act a quo, so there is no conflict of norms. The juridical implications of the basis and considerations of the Constitutional Court Decision for law enforcement in Indonesia, if used as evidence for wiretapping and recording, must comply with the law. However, in law enforcement this actually narrows the use of electronic documents/electronic information